Differences in maternal smoking across successive pregnancies – dose‐dependent relation to BMI z‐score in the offspring: an individual patient data (IPD) meta‐analysis. (23rd July 2018) - Albers, L.; von Kries, R.; Sobotzki, C.; Gao, H. J.; Buka, S. L.; Clifton, V. L.; Grzeskowiak, L. E.; Oken, E.; Paus, T.; Pausova, Z.; Rifas‐Shiman, S. L.; Sharma, A. J.; et al.
Summary: Introduction: Uncontrolled family factors may bias the estimation of the association between maternal smoking during pregnancy and offspring body mass index (BMI). The objective was to assess if there is an association between maternal smoking during pregnancy and offspring BMI z ‐score independent of factors in the siblings' shared environment and if such association is linear. Methods: We performed an individual patient data meta‐analysis using five studies providing sibling data (45, 299 children from 14, 231 families). In a multi‐level model, separating within‐family and between‐family effects and with random intercept for families, we analysed the dose–response association between maternal number of cigarettes per day during pregnancy and offspring's BMI z ‐score using B‐splines to allow for non‐linear associations. Results: A linear within‐family effect for number of cigarettes smoked in the range from 1 to 30 cigarettes per day on the offspring's BMI z ‐score was observed. Each additional cigarette per day between sibling pregnancies resulted in an increase in BMI z ‐score of 0.007 (95% CI [0.006, 0.009]). A between family‐effect emerged only with doses ≥25 cigarettes per day. Conclusions: The number of cigarettes mothers smoke per day during pregnancy is positively associated with offspring BMI z ‐score even among siblings, suggesting that the association is not entirely explained by confounding by family factors.